Internalization of Hadith on the Morals of the Prophet Muhammad for Character Building of Islamic Students - Iman Rasyid Maulana; Hendri Waluyo Lensa (IQRO: Journal of Islamic Education, 2026)
The decline of moral values among young people has become a major challenge for Islamic education, highlighting the need for character development based on authentic Islamic teachings. This study aims to analyze the moral values contained in the hadiths of the Prophet Muhammad SAW and examine their relevance to the formation of students' Islamic character. This research employed a qualitative library research approach by reviewing primary hadith sources and relevant classical and contemporary literature. Data were analyzed using content analysis to identify key moral values and their educational implications. The findings reveal that the hadiths emphasize essential values, including respect, compassion, brotherhood, honesty, responsibility, and ethical social interaction. These values are effectively internalized through three complementary approaches: exemplary conduct (uswah hasanah), direct practice (ta'dib), and moral instruction (da'wah). The study also demonstrates that these approaches are compatible with contemporary character education, particularly the dimensions of moral knowing, moral feeling, and moral action proposed by Lickona. It concludes that hadith-based character education provides a comprehensive framework for strengthening students' moral development. The findings imply that integrating prophetic moral values into curricula, learning activities, and school culture can reinforce students' moral resilience and support the development of individuals with strong Islamic character and ethical responsibility.